2020
DOI: 10.1101/2020.08.01.20162115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Study on Survival Scenario of COVID-19 patients in India: An Application of Survival Analysis on patient demographics

Abstract: The study of transmission dynamics of COVID-19, have depicted the rate, patterns and predictions of the pandemic cases. In order to combat the disease transmission in India, the Government had declared lockdown on the 25th of March. Even after a strict lockdown nationwide, the cases are increasing and have crossed 4.5 lakh positive cases. A positive point to be noted amongst all that the recovered cases are slowly exceeding the active cases. The survival of the patients, taking death as the event that varies o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Also, Oulhaj et al (2020) investigated the bias (through extensive simulations) in estimating the hazard ratio (HR) and the absolute risk reduction (ARR) of death when competing risks are ignored. Furthermore, Thai et al (2020), Salinas-Escudero et al (2020 and Kundu and Mandal (2020) employed survival analysis techniques to evaluate COVID-19 risk assessments in Vietnamese, Mexican and Indian populations, respectively. In the realms of exploring machine learning techniques, Atlam et al (2021) proposed a combination of autoencoder deep neural network and Cox regression to enhance prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Oulhaj et al (2020) investigated the bias (through extensive simulations) in estimating the hazard ratio (HR) and the absolute risk reduction (ARR) of death when competing risks are ignored. Furthermore, Thai et al (2020), Salinas-Escudero et al (2020 and Kundu and Mandal (2020) employed survival analysis techniques to evaluate COVID-19 risk assessments in Vietnamese, Mexican and Indian populations, respectively. In the realms of exploring machine learning techniques, Atlam et al (2021) proposed a combination of autoencoder deep neural network and Cox regression to enhance prediction accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Implementing survival analysis Castelnuovo et al (2020) found that impaired renal function, elevated C-reactive protein and advanced age were major predictors of in-hospital death in a large cohort of unselected patients with COVID-19, admitted to 30 different clinical centres all over Italy. Kundu and Mandal (2020) carried out a survival analysis to establish the variability in survivorship among age groups and sex at different levels that is national, state and district level in india. Ali et al (2020) implemented survival analysis to determine risk factors for death in patients with COVID-19 admitted to the main public sector hospital in Somalia and identify interventions contributing to improved clinical outcome in a low-resource and fragile setting.…”
mentioning
confidence: 99%